2018
DOI: 10.3390/nu10040499
|View full text |Cite
|
Sign up to set email alerts
|

Bioelectrical Impedance Phase Angle as an Indicator of Malnutrition in Hospitalized Children with Diagnosed Inflammatory Bowel Diseases—A Case Control Study

Abstract: The phase angle (PhA) seems to be a reliable screening tool for the identification of malnutrition risk in hospitalized children with inflammatory bowel disease (IBD). The aim of the present study was to assess the body composition and nutritional status of hospitalized children and adolescents with IBD by using bioelectrical impedance analysis (BIA) with phase angle (PhA) calculation, which has not been evaluated in hospitalized children with IBD yet. A total of 59 children and adolescents aged 4–18 years, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…In detail, our female patients had lower FFM values than controls, even though their BMI did not differ. Similar results were observed by Weich et al [35] in adolescent CD patients and by Filippi et al [36], who reported low FM in quiescent adult CD patients, while Valentini et al [37] did not find any differences in BC between healthy individuals and CD patients. A variety of methods can be employed to measure BC, such as dual energy X-ray absorptiometry (DXA), dilution techniques, BIA, air-displacement plethysmography (ADP) or magnetic resonance imaging (MRI), but none of them are error free [38].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In detail, our female patients had lower FFM values than controls, even though their BMI did not differ. Similar results were observed by Weich et al [35] in adolescent CD patients and by Filippi et al [36], who reported low FM in quiescent adult CD patients, while Valentini et al [37] did not find any differences in BC between healthy individuals and CD patients. A variety of methods can be employed to measure BC, such as dual energy X-ray absorptiometry (DXA), dilution techniques, BIA, air-displacement plethysmography (ADP) or magnetic resonance imaging (MRI), but none of them are error free [38].…”
Section: Discussionsupporting
confidence: 85%
“…Back et al [34] did not find any differences in PhA values between active and quiescent CD patients (p ¼ 0.75), while Wiech et al [35] showed that PhA was reduced in adolescent CD patients compared to the values of the controls. Interestingly, we found that PhA was inversely correlated with CDAI, age and FM, while it was positively associated with FFM and HGS, which was in accordance with previous results [5].…”
Section: Discussionmentioning
confidence: 93%
“…In Dutch research, the FFM and FM of 14 male and 18 female patients with ulcerative colitis were compared with those of the control group [ 27 ]. In recently published Polish research, the FFM and FM of 34 patients with ulcerative colitis and 25 patients with Crohn’s disease were assessed and compared with the values obtained from healthy subjects; however, the analyzed groups comprised only children and adolescents [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results were analyzed using dedicated software (Bodygram1_31 from AKERN, Pontassieve, Florence, Italy). Detailed description of methodology was described elsewhere [13].…”
Section: Methodsmentioning
confidence: 99%